Dynamic SDN Controller Placement in Elastic Optical Datacenter Networks - Liu, Yong; Gu, Huaxi; Yu, Xiaoshan; Zhou, Jiaying (2018 Asia Communications and Photonics Conference (ACP), 2018)
To solve the placement problem of SDN controllers in the elastic optical datacenter networks, most of researches focus on the static placement of controllers, which will lead to the load unbalancing of controllers under dynamic flow variations. Unfortunately, some controllers are not fully utilized so that it will result in a waste of controller resources. In this paper, we propose a dynamic matching algorithm called DMA which is able to optimize the controller load balance. Our solution, considering dynamic controller placement, is implemented for maximizing the control resource utilization, with the condition that the controller is not overloaded. Finally, compared with static placement, results of simulations demonstrate the viability of DMA in improving the control resource utilization.